The Influence of Principal’s Leadership and Work Motivation on the Performance of Public Elementary School Teachers - Riwayati, Ririn; Widayatsih, Tri; Suherman, Suherman (Journal of Social Work and Science Education, 2024)
This study aims to determine and analyze: (1) the influence of the principal’s leadership on teacher’s performance, (2) the effect of the principal’s work motivation on teacher’s performance. This research was conducted in eighteen public elementary schools in Rambang District, Muara Enim Regency, with a population of 153 people and a sample of 46 people (30%). The data analysis technique uses multiple linear analysis with simultaneous tests, the results show that the correlation coefficient or the influence generated is as large as the obtained R-Square value of 0.976, then the coefficient of determination is 97.6% and the remaining 2.4% is influenced by other factors that are not be this variable. The results of calculating the coefficients table obtained a b1 value of -0.047 and a b2 value of 1.096. Simultaneously these independent variables have an influence on the dependent variable.